Short Communication: Effect of different feed combination on the growth development of spotted cuscus (Spilocuscus maculatus) in captivity - MARTHA KAYADOE; ANA ROCHANA; UJANG HIDAYAT TANUWIRIA; SAULAND SINAGA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kayadoe M, Rochana A, Tanuwiria AH, Sinaga S. 2019. Short Communication: Effect of different feed combination on the growth development of spotted cuscus (Spilocuscus maculatus) in captivity. Biodiversitas 20: 526-531. One of the problems in maintaining cuscus in captivity was feed factor. Farmers had given various combinations of feed for cuscus, and several studies had been conducted on cuscus feed. For cuscus feed, it mostly used more than two types of feed, and the most dominant was banana. Inefficiency occurred fresh feed was prepared with more than two types. It can be costly, time-consuming and has more digestibility problem. Therefore, it was necessary to conduct an assessment by limiting the number of feed in two types to see the benefits of the ration (70% carbohydrate feed sources Musa paradisiaca var. mas and 30% from Pometia pinnata leaves, Pongamia pinnata leaves, Ipomoea aquatica, Brassica rapa var. parachinensis and Gryllus spp. The research was conducted for 36 days consisting of 2 periods, namely the adaptation period (5 days) and the data collection period (7 days), 3 times replications. The amount of feeding was limited based on 90% of adequacy of dry matter (preliminary research). The weighting of the initial body weight of cuscus and the final weight was carried out at the beginning and end of the period of data collection. Faecal was collected every day during the period of data collection. Each type of feed and fecal was analyzed for the dry matter. The results showed no significant effect (P>0.01) on dry matter consumption, but significantly affected the digestibility coefficients of dry matter. The preferred ration was 100% M. paradisiaca var. mas, which 49.99g/day, then a combination of M. paradisiaca var. mas with I. aquatica 48.187 g/day and M. paradisiaca var. mas combination with Averrhoa carambola (48.06 g/day), while the less preferred combination was M. paradisiaca var. mas with leaves from forest plants and combination of M. paradisiaca var. mas and animal protein feed sources i.e. Gryllus spp. However, the highest digestibility coefficient was achieved in 100% M. paradisiaca var. mas and M. paradisiaca var. mas combine with Gryllus spp. Furthermore, the relationship between digestibility coefficient and body weight gain showed that the combination of M. paradisiaca var. mas and Gryllus spp. had higher body weight gain compared to 100% Musa paradisiacal var. mas. Based on this study it was concluded that cuscus required a combination of carbohydrate feed sources and animal protein feed sources obtained from M. paradisiaca var. mas and Glyllus spp.